In Situ Atomic-Scale Investigation of Electromigration Behavior in Cu–Cu Joints at High Current Density - Huang, Hua-Jing; Wang, Chien-Hua; Wang, Che-Hung; Shen, Fang-Chun; Yang, Shih-Chi; Ong, Jia-Juen; Chiu, Wei-Lan; Chang, Hsiang-Hung; Chen, Chih; Wu, Wen-Wei (ACS nano, 2025)
Electromigration (EM) poses significant challenges to the reliability of miniaturized devices, particularly three-dimensional integrated circuits (3DICs) operating under high current densities. The EM phenomenon results from atomic-scale mechanisms involving momentum transfer between electron carriers and atoms. In this study, high-resolution transmission electron microscopy (HRTEM) was employed to investigate the atomic-scale behavior of EM in Cu–Cu joints. The analysis revealed that EM initially induced slip along various crystallographic planes, which gradually evolved into a stable slip along specific orientations, dominating the failure. This anisotropic atomic transport led to progressive degradation at the Cu–Cu bonding interface, including void formation and microstructural evolution. This interface depletion has been identified as a critical factor influencing the reliability of 3DIC packaging. Results emphasized the need for optimizing interconnect and interface properties to mitigate EM-induced failures, which is relevant to the development of high-power semiconductor technologies.